2023
DOI: 10.1002/cam4.5699
|View full text |Cite
|
Sign up to set email alerts
|

Cetuximab as third‐line rechallenge plus either irinotecan or avelumab is an effective treatment in metastatic colorectal cancer patients with baseline plasma RAS/BRAF wild‐type circulating tumor DNA: Individual patient data pooled analysis of CRICKET and CAVE trials

Abstract: The rechallenge strategy is based on the concept that a subset of patients with RAS wild‐type (WT) metastatic colorectal cancer (mCRC) could still benefit of epidermal growth factor receptor (EGFR) inhibition, after progression to an anti‐EGFR based‐therapy. We performed a pooled analysis of two‐phase II prospective trials to determine the role of rechallenge in third‐line mCRC patients with RAS/BRAF WT baseline circulating tumor DNA (ctDNA). Individual data of 33 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In prospective trials such as CHRONOS, CRICKET, and GEMCAD 17-01, patients with RAS/BRAF wild type were granted the opportunity for a therapeutic rechallenge if ctDNA testing revealed an absence of mutations in those genes. Those individuals who received personalised therapy based on their mutational status exhibited response rates ranging from 20 to 30% [39][40][41]. Therefore, monitoring guided by ctDNA facilitates the noninvasive molecular identification of patients within a subset of CRC who may exhibit a favourable response to anti-EGFR therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In prospective trials such as CHRONOS, CRICKET, and GEMCAD 17-01, patients with RAS/BRAF wild type were granted the opportunity for a therapeutic rechallenge if ctDNA testing revealed an absence of mutations in those genes. Those individuals who received personalised therapy based on their mutational status exhibited response rates ranging from 20 to 30% [39][40][41]. Therefore, monitoring guided by ctDNA facilitates the noninvasive molecular identification of patients within a subset of CRC who may exhibit a favourable response to anti-EGFR therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Because the trial is still ongoing, results have not yet been reported. Martini et al [ 35 ] conducted a pooled analysis of two prospective phase II trials, CAVE and CRICKET. Individual data of 33 and 13 patients from CAVE and CRICKET trials that received cetuximab rechallenge as third-line therapy were collected.…”
Section: Treatments Targeting Ras Statusmentioning
confidence: 99%